CRACKING THE CODING INTERVIEW - MCDOWELL LAAKMANN GAYLE (CALIFORNIA CAREERCUP, 2015)
"Cracking the Coding Interview" by Gayle Laakmann McDowell is the essential, must-have guide for software engineers preparing for technical interviews at top-tier tech companies like Google, Amazon, Microsoft, and Facebook. Authored by a former software engineer and interviewer at these companies, the book is a comprehensive resource that covers every facet of the modern tech interview process. It begins by demystifying the hiring process, offering "behind-the-scenes" insights, resume advice, and strategies for behavioral questions. However, its core value lies in its massive collection of 189 real programming interview questions and detailed walk-through solutions. These problems are strategically organized by key computer science topics, forcing candidates to master the fundamentals of data structures (like arrays, linked lists, trees, and hash tables) and algorithms (like sorting, searching, and dynamic programming). The book's primary goal isn't just to provide answers, but to teach a systematic problem-solving approach, enabling candidates to break down, analyze, and communicate solutions to complex problems they've never seen before.
CRACK CODING INTERVIEW
COMPUTERS
Keywords: COMPUTERS; COMPETITIVE